Pengaruh Penggunaan Media Gambar terhadap Kemampuan Menulis Puisi Siswa Kelas VIII SMPN 1 Tigo Nagari Kabupaten Pasaman - Juvrizal, Juvrizal; Ratna, Ellya; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article was written to detect the influence of picture media to thepoem writing skill of class 8th grade students of SMP Negeri 1 Tigo Nagari Kabupaten Pasaman.The data of this research were the results of the poem writing final test. The data were collected by giving poem writing test through picture media and without picture media. The hipotesist tested by using t-test formula. The results indicated that (1) the arithmetic average of the students’ poem writing skills experiment class were 75,19; (2) the arithmetic average of the students’ poem writing skills control class were 59,26; and (3) according to t-test’s results, can be concluded that there was a significant influence of the used of picture media to the poem writing skill of class 8th grade students of SMP Negeri 1 Tigo Nagari Kabupaten Pasaman.